Predictors of overweight and obesity in adult women in Nairobi Province, Kenya - Mbochi Regina W; Kuria Elizabeth; Kimiywe Judith; Ochola Sophie; Steyn Nelia P (BMC, 2012)
Abstract Background Since obesity in urban women is prevalent in Kenya the study aimed to determine predictors of overweight and obesity in urban Kenyan women. Methods A cross-sectional study was undertaken in Nairobi Province. The province was purposively selected because it has the highest prevalence of overweight and obesity in Kenya. A total of 365 women aged 25-54 years old were randomly selected to participate in the study. Results Higher age, higher socio-economic (SE) group, increased parity, greater number of rooms in the house, and increased expenditure showed greater mean body mass index (BMI),% body fat and waist circumference (WC) at highly significant levels (p <0.001). Most of the variance in BMI was explained by age, total physical activity, percentage of fat consumed, parity and SE group in that order, together accounting for 18% of the variance in BMI. The results suggest that age was the most significant predictor of all the dependent variables appearing first in all the models, while parity was a significant predictor of BMI and WC. The upper two SE groups had significantly higher mean protein (p <0.05), cholesterol (p <0.05) and alcohol (p <0.001) intakes than the lower SE groups; while the lower SE groups had significantly higher mean fibre (p <0.001) and carbohydrate (p <0.05) intakes. A fat intake greater than 100% of the DRI dietary reference intake (DRI) had a significantly greater mean BMI (p <0.05) than a fat intake less than the DRI. Conclusions The predictors of overweight and obesity showed that urbanization and the nutrition transition were well established in the sample of women studied in the high SE groups. They exhibited a sedentary lifestyle and consumed a diet high in energy, protein, fat, cholesterol, and alcohol and lower in fibre and carbohydrate compared with those in the low SE groups.